Plasma Pressures in the Heliosheath From Cassini ENA and Voyager 2 Measurements: Validation by the Voyager 2 Heliopause Crossing - Konstantinos Dialynas; Stamatios M. Krimigis; Robert B. Decker; Donald G. Mitchell (Geophysical Research Letters)
Abstract We report “ground truth,” 28‐ to 3,500‐keV in situ ion and 5.2‐ to 55‐keV remotely sensed ENA measurements from Voyager 2/Low Energy Charged Particle detector and Cassini/Ion and Neutral Camera, respectively, that assess the components of the ion pressure in the heliosheath. In this process, we predict an interstellar neutral hydrogen density of ∼0.12 cm−3 and an interstellar magnetic field strength of ∼0.5‐nT upstream of the heliopause in the direction of V2, that is, consistent with the measured magnetic field and neutral density measurements at Voyager 1 from August 2012, when the spacecraft entered interstellar space, to date. Further, this analysis results in an estimated heliopause crossing by V2 of ∼119 AU, as observed, suggesting that the parameters deduced from the pressure analysis are valid. The shape of the >5.2‐keV ion energy spectra play a critical role toward determining the pressure balance and acceleration mechanisms inside the heliosheath.